Impact of Injury Knowledge on The Incidence of Sports Injuries among Student-Athletes - I Nyoman Sukartidana; Johan Wahyudi; Kokom Supriyatnak; Maulidin Maulidin (Universitas Riau, 2025)
This observational study with a cross-sectional design analyzed the effect of injury management knowledge levels on injury incidence among 108 Undikma Physical Education student athletes selected via purposive sampling. Using a Guttman scale questionnaire and injury history, the data were analyzed using descriptive statistics, the Chi-square test, the t-test, and multivariate logistic regression. Descriptive results showed a very high injury incidence rate of 90.7% (mostly minor injuries), with an average knowledge score of 19.2 ± 2.8 on a 25-point scale. Bivariate analysis detected significant associations between educational history (p=0.048) and knowledge scores (p=0.002) and injury incidence. Furthermore, the final logistic regression model confirmed that educational history (OR=3.330; 95% CI: 1.026–10.803) and higher knowledge scores (OR=0.750; 95% CI: 0.610–0.922) acted as significant independent protective factors in reducing the risk of injury. Based on these findings, it is concluded that good understanding and exposure to effective education minimize the incidence of injuries among student-athletes; therefore, the implementation of a comprehensive and easily accessible injury management education program is a crucial recommendation that must be realized immediately.